Comparison of serum glycosylated hemoglobin levels in patients with diabetic cystoid macular edema with and without serous macular detachment - Turgut, Burak; Gul, Fatih Cem; Ilhan, Nevin; Demir, Tamer; Celiker, Ulku (All India Ophthalmological Soc, 2010)
Aim: A clinical comparative trial was conducted to compare the levels of glycosylated hemoglobin (HbA1c) in patients with diabetic cystoid macular edema (CME) with and without serous macula detachment (SMD). Materials and Methods: Thirty patients (group 1) with diabetic CME in both eyes, but without SMD, and 30 patients (group 2) with diabetic CME and SMD in both eyes documented by optical coherence tomography (OCT) and fundus fluorescein angiography (FFA), were included in the study. In addition to the measurement of central macular thickness by OCT and visual acuity (VA) (as logMAR) using the the early treatment diabetic retinopathy study (ETDRS) chart, the concentrations of HbA1c were measured by high performance liquid chromatography (HPLC). Statistical analysis was done by independent samples t test. Results: The mean logMAR VA was 0.8 +/- 0.22 (1.0-0.5) in group 1and 0.7 +/- 0.16 (1.0-0.6) in group 2. The mean central macular thickness, as determined by OCT, was 468.70 +/- 70.44 mu m (344-602 mu m) in group 1 and 477.80 +/- 73.34 mu m (354-612 mu m) in group 2. The difference between the groups was not statistically significant (P = 0.626). The mean HbA1c levels were 8.16 +/- 0.99% in group 1 and 10.05 +/- 1.66% in group 2. The difference between the groups was statistically significant (P < 0.001). Conclusions: The presence of SMD and high HbA1c levels in the patients with diabetic CME may be indirectly suggestive of retinal pigment epithelium dysfunction.
Keywords: Diabetic cystoid macula edema; HbA1c; retinal pigment epithelium dysfunction; serous macular detachment